Rancang Bangun Prototipe Detektor Gangguan Listrik Berbiaya Rendah Berbasis IP pada Kampus Institut Teknologi Sumatera - Saputra, Efa Maydhona; Ramadhani, Uri Arta (Department of Electrical Engineering, Faculty of Engineering, Universitas Lampung, 2022)
The ITERA electrical faults cannot be handled quickly by electricians due to the absence of a qualified monitoring system. It is also not possible to purchase a monitoring system with institutional scale because of the high price. Therefore, a low-cost electrical fault detector is designed with current sensor SCT013-000 as main device and communicates over an IP-based network. This detector is integrated with an electrical network information system that can be monitored via a web-browser. The system designed has succeeded in providing information on electrical disturbances with an average delay of 6 seconds and a maximum of 64 seconds when the detector loses its electricity supply. The price for a set of detectors with 2 sensors is around Rp. 249,500, it is relatively cheaper than similar products on the market.